Pengaruh Akuntansi Lingkungan Dan Kinerja Lingkungan Terhadap Kinerja Keuangan Pada Perusahaan Yang Mengikuti Program Penilaian Peringkat Kinerja Perusahaan Dalam Pengelolaan Lingkungan Hidup (Proper) - Aisyah Suhendra; Yusuf Faisal; Soleha (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2022)
This research test the influence of the environtmental accounting (EAPI) and environtmental performance (PROPER) from financial performance . Financial performance using return on assets from financial statement that adopt PROPER and listed at Indonesia Stock Exchange (IDX) in 2017 and 2018. The results of multiple regression of 94 sample showed that only environtmental performance have impact while envireontmental accounting have no impact to financial performance